2000
DOI: 10.1128/jcm.38.2.752-754.2000
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Oxacillin MIC with mecA Gene Carriage in Coagulase-Negative Staphylococci

Abstract: The National Committee for Clinical Laboratory Standards has recently changed the oxacillin breakpoint from ≥4 mg/liter to ≥0.5 mg/liter to detect methicillin-resistant coagulase-negative staphylococci (CoNS) because the previous breakpoint lacked sensitivity. To determine the correlation between the new oxacillin breakpoint and the presence of themecA gene, 493 CoNS of 11 species were tested. The presence of the mecA gene was determined by PCR, and oxacillin susceptibility was determined by the agar dilution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(38 citation statements)
references
References 18 publications
7
30
1
Order By: Relevance
“…The combination between these tests improved the sensitivity for detecting oxacillin resistance in CoNS as well as a negative predictive value. As expected, the sensitivity and specificity of the tests used for S. aureus are lower for CoNS strains because standard susceptibility testing is less accurate in determining oxacillin resistance in mecA-positive CoNS than in MRSA (Hussain et al, 2000;Caieirão et al, 2004;Ghoshal et al, 2004).…”
Section: Resultsmentioning
confidence: 53%
“…The combination between these tests improved the sensitivity for detecting oxacillin resistance in CoNS as well as a negative predictive value. As expected, the sensitivity and specificity of the tests used for S. aureus are lower for CoNS strains because standard susceptibility testing is less accurate in determining oxacillin resistance in mecA-positive CoNS than in MRSA (Hussain et al, 2000;Caieirão et al, 2004;Ghoshal et al, 2004).…”
Section: Resultsmentioning
confidence: 53%
“…The oxacillin MIC breakpoints for CoNS recommended by NCCLS are ‡ 0.5 mg ⁄ L for resistance and £ 0.25 mg ⁄ L for susceptibility when using the agar dilution method [30]. Hussain et al [30] found that many isolates of S. lugdunensis have oxacillin MICs of 0.5-2 mg ⁄ L (i.e., resistant according to NCCLS guidelines); however, these isolates were mecA-negative. Only one mecApositive isolate of S. lugdunensis has been reported, with an oxacillin MIC of > 256 mg ⁄ L [22].…”
Section: Discussionmentioning
confidence: 99%
“…The detection of oxacillin resistance in staphylococci is complex and time-consuming because of the heterogeneous nature of mecA gene expression. Furthermore, in some species of CoNS the differentiation between mecA-negative and mecA-positive strains may not be possible by susceptibility methods (11). Alternative methods for rapid and accurate detection of oxacillin-resistant strains are desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Overnight growth from plates containing Columbia agar supplemented with 5% sheep blood was used to perform a PCR for the nuc and mecA genes. DNA extraction, PCR master mixture concentrations, and amplification conditions were described previously (11). The primers used to detect the nuc and mecA genes were published previously (4,18).…”
Section: Methodsmentioning
confidence: 99%